HUBUNGAN ANTARA KORUPSI DENGAN PERKEMBANGAN PASAR SAHAM DAN PERBANKAN: KAJIAN EMPIRIS PADA SEMBILAN NEGARA DIKAWASAN ASEAN+3 - Muhammad Fazri; Hermanto Siregar; Heni Hasanah (Jurnal Ekonomi Pembangunan, 2017)
Banking and stock market are two financial institutions which play an important role in the economic development process. Many studies suggest that the development of banking and stock market are able to increase the economic growth. There are factors which influence the development of these two financial institutions, for example macroeconomic stability and institutional influences such as corruption. This study aims to analyze how corruption affects the development of banking and stock market and also tries to identify the role of development of banking to reduce corruption. This study uses panel data for nine countries of ASEAN +3 region, during 2003-2012. The result shows that corruption hinders the development of banking and stock market. In addition, banking development will reduce corruption.